Aliens and Englishness in Elizabethan drama - Kermode, Lloyd Edward (Cambridge Univ. Press, 2009)
Aliens and the English in London -- Discovering the alien in Elizabethan moral drama -- Accommodating the alien in mid-Elizabethan London plays -- Incorporating the alien in Shakespeare's second tetralogy -- Being the alien in late Elizabethan London plays -- Early modern and post-modern alien excursions